PENGARUH KEPUASAN KERJA DAN KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASIONAL DAN KUALITAS LAYANAN PADA PERUM DAMRI CABANG MATARAM - erlan erlan (Master of Management, Mataram University, 2017)
Service quality is one important part in a service company such as Perum Damri Branch Mataram. This research is aimed at (1) analyzing the significant effect of work satisfaction on the organization commitment, (2) analyzing the significant effect of leadership on the organization commitment, (3) analyzing the significant effect of work satisfaction on the service quality, (4) analyzing the significant effect of leadership on the service quality, (5) analyzing the significant effect of the organizational commitment on the service quality. This research is associative causal study. The data were collected through questionnaires distributed for census to the population of 104 employees of Perum Damri. The data were analyzed with path analysis with Amos 2.1 for windows. The research showed that (1) work satisfaction has positive and significant effect on the organizational commitment, (2) leadership has positive but not significant effect on the organizational commitment, (3) work satisfaction has positive and significant effect on the service quality, (4) leadership has positive but not significant effect on the service quality, (5) the organizational commitment has significant effect on the service quality. Keywords : work satisfaction, leadership, organisasional commitment, service quality